Pengaruh Perilaku Keuangan, Pengetahuan Investasi Dan Toleransi Risiko Terhadap Keputusan Investasi Di Pasar Modal (Studi Kasus Pada Mahasiswa Fakultas Ekonomi dan Bisnis Universitas Islam Malang - Azizah, Wahyu Nur; Wahono, Budi; Bastomi, Mohamad (UNIVERSITAS ISLAM MALANG, 2024)
Abstract This research for know The influence behavior finance , knowledge investment and tolerance risk to decision investment in the capital market. This Study supported by the theory of planned behavior which states that intention influenced by attitude individual. Population is student faculty Islamic University of Economics and Business poor thing. Determination sample using non probability sampling with purposive sampling approach. Data collection in research This use method questionnaire. Amount sample calculated use formula slovin and acquire results of 100 respondents. Characteristics sample used is students who have do transactions in the capital market at least one time. Data analysis techniques used in study This is instrument test analysis, normality test, assumption test classic, analysis multiple linear regression, t test, F test and coefficient test determination with data processing using SPSS 22.0 software. Keywords: Behavior Finance, Knowledge Investment, Tolerance Risk, Investment Decisions, Theory Of Panned Behavior